Proteomic Analysis of Soybean [Glycine max (L.) Merrill] Roots Inoculated with Bradyrhizobium japonicum Strain CPAC 15 - Torres, Adalgisa R (Libertas Academica, 2013)
This research intended to analyze the expression pattern of proteins in roots of the Brazilian soybean cultivar Conquista when inoculated with Bradyrhizobium japonicum CPAC 15, a strain broadly used in commercial inoculants in Brazil. At ten days after bacterial inoculation, whole-cell proteins were extracted from roots and separated by 2-D gel electrophoresis. Comparative analysis revealed significant changes in the intensity of 37 spots due to the inoculation (17 up-regulated and 20 down-regulated proteins), identified by MALDI-TOF/TOF-TOF. Identified proteins were associated with COG functional categories of information storage and processing, cellular processes and signaling, metabolism, and also in the “poorly characterized” and “not in COG” categories. Among the up-regulated proteins, we identified sucrose synthase (nodulin-100), β-tubulin, rubisco activase, glutathione-S-transferase, a putative heat-shock 70-kDa protein, pyridine nucleotide-disulphideoxidoreductase and a putative transposase. Proteomic analysis allowed for the identification of some putative symbiotic functions and confirmed the main biological processes triggered in the nitrogen-fixing symbiosis with soybean.